2022
DOI: 10.1021/jacsau.2c00484
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Cerium(III)/(IV) Structures and Charge-Transfer Mechanism in Sulfuric Acid

Abstract: The Ce3+/Ce4+ redox couple has a charge transfer (CT) with extreme asymmetry and a large shift in redox potential depending on electrolyte composition. The redox potential shift and CT behavior are difficult to understand because neither the cerium structures nor the CT mechanism are well understood, limiting efforts to improve the Ce3+/Ce4+ redox kinetics in applications such as energy storage. Herein, we identify the Ce3+ and Ce4+ structures and CT mechanism in sulfuric acid via extended X-ray absorption fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…70 In addition, the cerium 4f-electron is available for charge transfer in redox activity or bonding, thus facilitating the conversion within Ce( iv ) and Ce( iii ). 71 This characteristic may also promote a surface cooperative effect with the Pt in the CeO 2 –Pt interface through electron transfer reactions via redox mediation. The reduction peak of Ce was observed at 0.6 V under alkaline conditions, as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…70 In addition, the cerium 4f-electron is available for charge transfer in redox activity or bonding, thus facilitating the conversion within Ce( iv ) and Ce( iii ). 71 This characteristic may also promote a surface cooperative effect with the Pt in the CeO 2 –Pt interface through electron transfer reactions via redox mediation. The reduction peak of Ce was observed at 0.6 V under alkaline conditions, as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the early metal cations used together with the semiconductor under photo-excitation is a system composed of TiO 2 (n-type semiconductor) and Ce cations [7][8][9]. Since then many have investigated such a system, mostly in the solid state, however [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yan et al reported that W-doped α-Ni­(OH) 2 presents outstanding electrocatalytic activity, and W could work as the active site for the water splitting reaction. Ce commonly exhibits the reversible reaction accompanied by the redox pairs, and it is a class of dopant ions with the desirable compatibility . Moreover, the radius of the Ce 3+ ion (102 pm) is significantly larger than that of the Ni 2+ ion (69 pm), so the dopant Ce would lead to the increase of the Ni–O bond length and the d -spacing, where the looser lattice structure might solve the stability problems caused by phase transition. , Therefore, it is feasible to introduce Ce ions in Ni­(OH) 2 to establish a stable system for HMF oxidation.…”
Section: Introductionmentioning
confidence: 99%